As representações de educação feminina nos textos de Maria Dimpina Lobo Duarte (1916-1950) - Albuquerque, Dálete Cristiane Silva Heitor de (2023)
ABSTRACT: This doctoral thesis is the result of an investigation developed in the Postgraduate Program in Education at Federal University of Mato Grosso. The study is part of the bibliographical productions carried out by the Research Group in History of Education and Memory (GEM), linked to researches in the area of Culture, Memory and Theories in Education. The research reveals the expressiveness of the magazine A Violeta in the city of Cuiabá, in its early years in the 20th century, and which would stand out for its political potential, for being an authorial production of women-authors, members of an economic elite and literate, at a time when women were silenced, and their deeds did not compose historiographical reports. In this sense, this study aims to analyze the representations of women education disseminated in the writings of one of these womenauthors - Maria Dimpina Lobo Duarte, who excelled in this magazine with her dense textual production, especially on the theme of Education. The temporal cut adopted covers the years 1916 to 1950 and was chosen taking into account the circulation period of the magazine A Violeta. This was an important feminine magazine in Mato Grosso, written by and for women and where Maria Dimpina publicized her project of women education, of training women for housework. The theoretical references used: (1) the concept of Representations, proposed by Chartier (1988), placing this study in the field of Cultural History; (2) still, the concept of Model Reader, by Umberto Eco (1986), a concept that helped in understanding this textual strategy in the figure of the woman model reader of the texts analyzed in the magazine; (3) also, a paratextual analysis, based on the studies of Gérard Genétte (2009), in order to understand the material aspects of the magazine. The research had as privileged source the texts of Maria Dimpina Lobo Duarte in the magazine A Violeta, mainly those ones published in the sections “Chrônica” and “Correspondência de D. Martha”, respectively. As result, it can be seen that the active voice and constant presence in the socio-political movements in which Maria Dimpina engaged, through her texts and evidenced a conservative posture for women education, in full agreement with her time, despite to be at the forefront in discussions for the modernity of her city. In seeking to understand her writings as a discursive space and an opinion leader and behaviors of her readers, it was possible to realize principles of training women for home, a women education for work, but in such a way that women remain responsible for moral education of their children and also responsible for domestic governance.